Формирование приоритетов интенсификации факторов производства угольного предприятия на основе структурно-иерархического анализа - Давлианидзе, Я.С. (Економіка промисловості, 2013)
Проведено оцінку взаємного впливу чинників виробництва і пріоритетів їх формування на базі підприємств вугільної галузі на основі структурно-ієрархічного підходу. Обґрунтовано можливості йі умови аналізу багатоваріантності впливів чинників праці і капіталу на зниження трудомісткості і капіталомісткості очисних робіт. Доведено доцільність застосування методу аналізу ієрархій, за допомогою якого побудовано матриці парних порівнянь.
Ключові слова: інтенсифікація чинників виробництва, матриця попарних порівнянь, метод аналізу ієрархій, структурно-ієрархічний метод, чинники виробництва. Проведена оценка взаимного влияния факторов производства и приоритетов их формирования на базе предприятий угольной отрасли на основе структурно-иерархического подхода. Обоснованы возможности и условия анализа многовариантности воздействия факторов труда и капитала на снижение трудоемкости и капиталоемкости очистных работ. Доказана целесообразность применения метода анализа иерархий, с помощью которого построены матрицы парных сравнений.
Ключевые слова: интенсификация факторов производства, матрица попарных сравнений, метод анализа иерархий, структурно-иерархический метод, факторы производства. In new economics which is based on the knowledge system the level and complicity of innovation development of industrial complexenterprise is determined by such deep transformational phenomena as change of structure of technological modes in world economy, change of qualitative and quantitative proportions of production factors and, in particular, intensification of production factors, which is able to solve such actual problem as migration to primary intensive way of development. That is why the purpose of this research is development and improvement of methodological approach to formation of priority variants of production factors intensification on the basis of method of hierarchies analysis. For solution ofthis task the method of hierarchies analysis is usedwhich is systematic procedure for hierarchical expressing the elements determining the essence of any problem.
The assessment of mutual influence of production factors and priorities of their formation by the example of coal industry enterprise on the basis of structural-hierarchic approach is given in the article. On the basis of structural-hierarchic approach the criteriawere formed, which, each in different ways and with different level of intensity, make influence on meaning of coal enterprise factors. There were proved the possibilities and conditions of multipart influence of labor factors and capital on decrease of labor and capital intensity of coal-face works, which will allow giving rise in increasing effectiveness while securing necessary labor safety. Practicability of method of hierarchies analysis, with the help of which the comparison-of-pairs matrix were built, was proved. Investigation conducted allowed choosing the directions of capital investments for the purpose of getting maximum effect.
Keywords: production factors intensification, comparison-of-pairs matrix, method of hierarchies analysis, structural-hierarchic method, production factors.